Uniting souls, discussing the nation, imposing oneself: gender, war and literature in correspondence sent by Teresa González de Fanning to José Enrique Rodó (18971901) - Santos, Elisangela da Silva [UNESP] (Arquivo Nacional, 2024)
The text presents and discusses the letters from the Peruvian writer Teresa Gonz & aacute;lez de Fanning sent to the Uruguayan writer Jos & eacute; Enrique Rod & oacute;. Our proposal is to reopen the archives to reveal an important facet of the author's epistolary: the presence of women reflecting on the national and continental destiny. We conclude that the missives fulfill the role of bringing us closer to the theme of intellectual sociability of an author who accessed writing as a form of cultural and political expression.
Keywords: Teresa Gonz & aacute;lez de Fanning; correspondence; literary sociability; Jose Enrique Rod & oacute